النظر في الظالم منذ عهد الرسول صلى الله عليه و سلم و حتى نهاية العهد الأموي - الفاعوري، أمجد ممدوح محمد Alfaouri, Amjd Mamdouh Mohammed; القرالة، عمر محمد (جامعة القدس المفتوحة, 2014)
تهدف هذه الدراسة إلى إبراز دور نظر المظالم تاريخياً في صدر الإسلام حتى نهاية الدولة الأموية، ويُعد النظر في المظالم من المظاهر الإيجابية في الدولة العربية الإسلامية عبر مسيرتها التاريخية، ومفخرة من مفاخر النظام القضائي الإسلامي ،وواحد من أبرز مظاهر الحضارة العربية الإسلامية لما له من أهمية كبيرة في إحقاق الحق، وإقامة العدل ودفع التخاصم بين الناس على اختلاف أصولهم. تناولت هذه الدراسة نشأة النظر في الظالم وتطوره واختصاصات الناظر فيه والدور الذي قام به لحماية مبدأ الشرعية وتأكد العدالة . إن ولاية أمور الناس، وإقامة العدل ومنع الظلم عنهم، من أعظم واجبات الدين، بل لا قيام للدين إلا بها. ولأن الله سبحانه وتعالى أوجب الأمر بالمعروف والنهي عن المنكر، فإنه أوجب كذلك العدل، ونصرة المظلوم، وهو ما لا يتم إلا بالإمارة والقوة، فإنه لا ملك إلا بدين ،ولا دين إلا بملك. This study aims to present the role of trying the grievances historically in the early Islamic period until the end of the Umayyad state. Trying the grievances is considered one of the positive aspects in the Arabic Islamic state during its historical path, one of the prides of the Islamic legal system and one of the most prominent aspects of the Arabic Islamic civilization, because of its great importance in the enforcement of the law, the administration of justice and the ending of the litigation between people from different origins. This study dealt with the growth of trying the grievances, its development, the functions of its supervisor and his role in protecting the principle of the legitimacy and the confirmation of justice. The ruling of people is important. The practice of justices and the prevention of injustice are the greatest duties of religion without which it can’t rise. Religion encourages calling for doing good things and abandoning bad things. Religion helps justice to prevail. This is possible through power and there is no religion without power
Keywords: مجلس المظالم -- ديوان المظالم -- السلطة القضائية -- عصر النبوة -- العصر الأموي -- عصر الخلفاء الراشدين -- النظر في المظالم -- أجور العمال